Establishment of a real time RT-PCR assay to detect expression of selected genes from multiple-drug resistant Acinetobacter Baumannii / Sanaz Koosha - Koosha, Sanaz (2014)
Acinetobacter baumannii has an important role in nosocomial infections. However, in addition to the respiratory infections caused by this bacterium it also causes other infections, such as, bacteremia, urinary tract infections, meningitis, eye and skin infections. Recently the antibiotic resistance of A. baumannii has increased in respect of almost all of the current antibiotics. The present study focuses on the expression of genes ABAYE0161 (hypothetical protein) and ABAYE3501 (general secretion pathway protein C) in the presence and absence of the antibiotic imipenem. These two genes were chosen from the previous studies concerning the effect of microgravity on the expression of A. baumannii genes. The multiple antibiotic resistant strain of A. baumannii was collected from a patient at University of Malaya Medical Centre (UMMC) in 1996. The identity of the tested strain was confirmed by sequencing and analysing of the 16S rDNA gene. The quality and quantity of the extracted RNA were checked out and the related cDNA was synthesized. Real time RT-PCR was done in the last step to evaluate the expression of the interested gene. In comparing our findings and the results from the microgravity study, we found that imipenem reduces the expression of the ABAYE0161 and ABAYE3501 genes, while microgravity has an inhibitory effect on ABAYE0161 and enhances ABAYE3501 gene expression.